(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
mechanism and kinetics are developed for the initiated nonbranched-chain formation of ethylene glycol in methanol–formaldehyde solutions at formaldehyde concentrations of 0.1–3.1 mol dm–3and temperatures of 373–473 K. The experimental concentrations of the free unsolvated form of formaldehyde are given at the different temperatures and total concentrations of formaldehyde in methanol. The experimental dependence of the radiation-chemical yields of ethylene glycol on formaldehyde concentration in γ-radiolysis of methanol–formaldehyde solutions at 373– 473 K is shown. At a formaldehyde concentration of 1.4 mol dm–3and T = 473 K, the radiation-chemical yield of ethylene glycol is 139 molecules per 100 eV. The effective activation energy of ethylene glycol formation is 25 ± 3 kJ mol–1. The quasi-steady-state treatment of the reaction network suggested here led to a rate equation accounting for the nonmonotonic dependence of the ethylene glycol formation rate on the concentration of the free (unsolvated) form of dissolved formaldehyde. It is demonstrated that the peak in this dependence is due to the competition between methanol and CH2=O for reacting with the adduct radical HOCH2CH2O•.